2003
DOI: 10.1046/j.1523-1755.2003.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine counteracts nitric oxide deficiency and improves the recovery phase of ischemic acute renal failure in rats

Abstract: Ischemic ARF is accompanied by marked alterations in the expression of key enzymes of the nitric oxide pathway, indicative for deficiency of constitutive NOS activity. l-Arg supplementation reduces O2- generation and significantly improves the expression of nitric oxide signaling proteins as well as the recovery phase of ischemic ARF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
71
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 45 publications
12
71
0
3
Order By: Relevance
“…Experiments were performed as published recently (24,27), where I/R injury was induced by bilateral clamping of renal arteries for 45 min. Female Sprague-Dawley rats (200 to 250 g body wt) were obtained from Charles River (Kissleg, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments were performed as published recently (24,27), where I/R injury was induced by bilateral clamping of renal arteries for 45 min. Female Sprague-Dawley rats (200 to 250 g body wt) were obtained from Charles River (Kissleg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Inulin and PAH clearances were determined as described recently (27). Thereafter, net secretion of PAH (PNS) was calculated as described below.…”
Section: Measurement Of Clearances and Pah Net Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of nitric oxide (NO) in renal IR injury has been extensively investigated (8,26,28,34,41,46,50). However, the involvement of the NO downstream signaling pathway, cGMP and cGMP-dependent protein kinase (PKG), in renal IR injury has not been investigated.…”
mentioning
confidence: 99%
“…In another study, Weight et al (16) emphasized that L-NAME causes no significant alteration in the histology in rats that underwent renal I/R. Schneider et al (17) suggested that in vivo acute L-arginine administration has Table 1. Statistically data with matched normal dissociation favorable effects on renal ischemia.…”
Section: Lahera Et Al (4) Performed Hemodynamic Examinations To Keepmentioning
confidence: 99%